Sozdar, She Who Lives Her Promise - Wietsma, Annegriet (Netherlands : Bonanza Films, 2007)
Nuriye Kesbir refused to be given in marriage when she was twelve. Thirty years later she is still fighting, but now as a wanted leader of a guerrilla-movement - the Kurdish PKK. Why does a woman turn her back on marriage and motherhood to choose a path that leads to a life and death battle instead? “Sozdar, she who lives her promise” is a film about a stubborn Kurdish woman who ended up on a road of no return because of her personal choices. The filmmaker follows Kesbir on her remarkable journey that begins in a Dutch prison and ends in the rough mountains of Northern Iraq.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films